OPTIMALISASI KETERAMPILAN MICROSOFT EXCEL BAGI SANTRI PONDOK PESANTREN TAHFIZH AL-QURAN DAARUL HIKMAH CIPUTAT TANGERANG SELATAN MELALUI PELATIHAN LANJUTAN - Nurhayati; Eka Yuni Titik Artaningsih; Adam Muiz (Abdi Jurnal Publikasi, 2025)
The ability to use data processing software such as Microsoft Excel is an important skill that all students should acquire—including those studying in Islamic boarding schools (pesantren). However, limited access to technology training in many pesantren has led to a situation where most santri only understand the basic functions of Microsoft Excel. This community service program was designed to improve the santri's advanced Excel skills at Pondok Pesantren Tahfizh Al-Qur’an Daarul Hikmah in Ciputat, South Tangerang. The focus was on supporting administrative data management within the pesantren. The training method combined interactive lectures, live demonstrations, and hands-on practice with advanced Excel formulas such as IF, VLOOKUP, COUNTIF, and SUMIF, as well as the use of data visualization tools. To evaluate learning outcomes, we used questionnaires and direct observation to assess participants’ understanding and practical skills. The results showed a significant improvement in participants’ ability to use advanced Excel features effectively. They also demonstrated increased confidence and efficiency in managing administrative data. Notably, the number of participants exceeded expectations, with strong engagement throughout the sessions. Beyond skill development, the training raised awareness among santri about the importance of mastering digital tools as a critical asset for their future careers. In conclusion, the program proved to be an effective model for technology-based empowerment in pesantren settings. It is hoped that this initiative will continue in the future to reach a wider and more lasting impact.